The Role of Culture in Moderating the Influence of Financial Literacy and the Performance of SMEs in North Toraja Regency - Stefani Marina Palimbong; Mince Batara (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research aims to analyze and determine the role of culture in moderating the influence of financial literacy on SME performance. This research uses a quantitative approach. The objects studied were SME owners in Toraja Regency. Data was obtained through a survey with an instrument, namely a questionnaire and the sampling method used was the simple random sampling method. The results of the research conclude that financial literacy has a significant effect on the performance of North Toraja Regency MSMEs and culture can moderate the influence of financial literacy on the performance of North Toraja Regency SMEs.